1976
DOI: 10.1037/0278-7393.2.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Reading a year later.

Abstract: Two sets of measurements evaluated performance on typographically inverted text that students had learned to read 13 to IS months earlier. In one set, speed of reading was compared for pages read for the first and second times. Reread pages were read more quickly, thereby revealing an exceptional degree of memory at the pattern-analyzing level. In the second set of measurements, the readers classified the pages as to occasion of reading. Comparing the two sets of measurements showed that different aspects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
290
3

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(319 citation statements)
references
References 20 publications
26
290
3
Order By: Relevance
“…Certainly, this explanation would be consistent with theories proposing abstract representations. Rather than speculating that talker and rate characteristics are preserved in memory representations per se, effects of variation on recognition memory could be due to the retention of the compensatory procedures that are used to abstract the linguistic identity of each word (Kolers, 1976;Kolers & Ostry, 1974). Thus, speaking rate and talker might have greater effects on memory performance than overall amplitude simply because these sources of variability require more extensive processing operations at the time of initial encoding that, once learned, would more greatly facilitate processing when repeated.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, this explanation would be consistent with theories proposing abstract representations. Rather than speculating that talker and rate characteristics are preserved in memory representations per se, effects of variation on recognition memory could be due to the retention of the compensatory procedures that are used to abstract the linguistic identity of each word (Kolers, 1976;Kolers & Ostry, 1974). Thus, speaking rate and talker might have greater effects on memory performance than overall amplitude simply because these sources of variability require more extensive processing operations at the time of initial encoding that, once learned, would more greatly facilitate processing when repeated.…”
Section: Discussionmentioning
confidence: 99%
“…People spontaneously remember the presentation modalities of words (Hintzman, Block, & Inskeep, 1972;Hintzman, Block, & Summers, 1973;Kirsner, 1974;Lehman, 1982;Light, Stansbury, Rubin, & Linde, 1973), the spatial location of information in text (Lovelace & Southall, 1983;Rothkopf, 1971), and the exact wording of sentences (Begg, 1971;Keenan, MacWhinney, & Mayhew, 1977). Experiments on transformed text show the persistence of font details in memory after reading (Kolers, 1976;Kolers & Ostry, 1974), and similar findings occur with isolated printed words Kirsner, 1973;Roediger & Blaxton, 1987;Tenpenny, 1995). Given these data, Jacoby and Hayman (1987) suggested that printed word perception relies on episodic memory.…”
Section: Speaker Normalizationmentioning
confidence: 93%
“…Instead, it appeared more informative to use weIl-EXPLICIT AND IMPLICIT MEMORY 79 known procedures. Mirror drawing (Kolers, 1976), face identification (Ellis, Young, Flude, & Hay, 1987), and picture naming (Carroll et al, 1985) were not included because they involve material other than words, and lexical decision (Scarborough et al, 1977) was discarded because it involves a number of additional processing steps that are linked to decision processes (e.g., Lorch, 1986).…”
mentioning
confidence: 99%